Love Monster and the last chocolate - Bright, Rachel (New York : Farrar Straus Giroux, 2015)
When Love Monster receives a box of chocolates as a gift, he has second thoughts about sharing them with all of his friends.
Keywords: Monsters -- Fiction; Sharing -- Fiction; Chocolate -- Fiction